2003
DOI: 10.1046/j.1365-2362.2003.01125.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐density‐lipoprotein peak particle size in a Mediterranean population

Abstract: In this population, which appears to be somewhat protected by premature coronary artery disease, a low prevalence of the LDL pattern B was found in both men and women, and plasma TG could have a key role in regulating the LDL peak particle size. The follow up, still ongoing, will provide useful information on the predictive role of LDL peak particle size on cardiovascular risk, at least in a low-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(4 citation statements)
references
References 38 publications
2
0
2
Order By: Relevance
“…Diabetic dyslipidemia is characterized by the elevated TG and sdLDL, decreased HDL-C and slightly elevated or normal LDL-C. A study shows that the ratio of sdLDL/LDL in healthy male adults is about 30% to 35%, whereas it reaches as high as 45% to 50% in diabetic subjects. [43,44] Similar results were reported in a Japanese study. [45] In our study, results showed no significant difference in LDL-C within the general population, but higher sdLDL was found in the diabetic subgroup.…”
Section: Discussionsupporting
confidence: 88%
“…Diabetic dyslipidemia is characterized by the elevated TG and sdLDL, decreased HDL-C and slightly elevated or normal LDL-C. A study shows that the ratio of sdLDL/LDL in healthy male adults is about 30% to 35%, whereas it reaches as high as 45% to 50% in diabetic subjects. [43,44] Similar results were reported in a Japanese study. [45] In our study, results showed no significant difference in LDL-C within the general population, but higher sdLDL was found in the diabetic subgroup.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, the prevalence of sdLDL among healthy non-diabetics in a small Mediterranean Island was determined to be 30 – 35% of total LDL-C in adult men. [ 34 ] This study reported 32% of LDL-C as sdLDL-C among non-diabetic men which is almost the same as the Mediterranean study. Among diabetes patients, a slightly higher prevalence of 50% was reported [ 34 ] which is higher than the 45% noted in this study.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, since the immediate pre-MI, LDL-cholesterol levels were not available, we cannot rule out the possibility that prior to MI these values were higher than after the MI event. Triglycerides levels have been reported to increase small, dense LDL particles and therefore the risk of cardiovascular disease [58, 59]. In the present study, however, a significant difference is not observed.…”
Section: Discussioncontrasting
confidence: 82%
“…The exclusion of this outlier from the analysis did not alter the distribution of these data or result in a significant difference in triglyceride levels between the 2 groups. Since there is no difference between groups in triglyceride levels, the hypothesized difference in the LDL subfraction profile in our 2 groups may be mediated by other factors such as smoking [58-60]. In contrast to the above hypotheses, no correlation was observed between smoking and triglyceride level in this study, or between MI occurrence and triglyceride level.…”
Section: Discussioncontrasting
confidence: 60%